2008
DOI: 10.1002/pssc.200779230
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of self‐heating in AlGaN/GaN HFETs using thick AlN surface passivation films

Abstract: We have fabricated and investigated AlGaN/GaN heterojunction field‐effect transistors (HFETs) with thick AlN surface passivation films. The HFETs exhibit increased drain currents and the transconductances with suppression of the self‐heating‐induced negative differential conductance at high applied voltages. Since the effects are more prominent for thicker AlN films, we conclude that the AlN films cause not only surface passivation, but also self‐heating reduction. (© 2008 WILEY‐VCH Verlag GmbH & Co. KGaA, Wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…12 Selfheating had also been addressed using heat spreading layers such as thick AlN surface passivation films. 13 Using flexible graphene quilts precisely transferred over the drain contacts, Yan et al demonstrated lowering the hotspot temperature by as much as 20 C. 14 Various flip-chip bonding techniques have also been shown to be effective in improving thermal performance of AlGaN/GaN HEMTs. 15,16 In this Letter, we report dramatic reduction of thermal resistance in AlGaN/ GaN MMC HEMTs fabricated on sapphire substrates.…”
mentioning
confidence: 99%
“…12 Selfheating had also been addressed using heat spreading layers such as thick AlN surface passivation films. 13 Using flexible graphene quilts precisely transferred over the drain contacts, Yan et al demonstrated lowering the hotspot temperature by as much as 20 C. 14 Various flip-chip bonding techniques have also been shown to be effective in improving thermal performance of AlGaN/GaN HEMTs. 15,16 In this Letter, we report dramatic reduction of thermal resistance in AlGaN/ GaN MMC HEMTs fabricated on sapphire substrates.…”
mentioning
confidence: 99%
“…The AlN and SiN films were deposited by RF magnetron sputtering using an AlN and Si 3 N 4 target, respectively. Although the sheet resistance was increased due to the sputtering process damage, this can be eliminated by thermal annealing in N 2 ambient [3]. After the thermal annealing, sheet resistances are 780 Ω/ and 470 Ω/ for AlN and SiN passivation, respectively.…”
Section: Device Fabricationmentioning
confidence: 99%
“…Recently, AlN surface passivation for AlGaN/GaN heterojunction field effect transistors (HFETs) on sapphire substrates has been investigated [1][2][3], because the high thermal conductivity of AlN, which is ∼ 200 times higher than that of SiN, is effective to reduce the self-heating of the HFETs. In fact, DC measurements showed the reduction of the self-heating, as well as the suppression of the current collapse, by the AlN passivation.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their high thermal conductivities, the nitride materials are favorable also for passivation of GaN-based devices, exhibiting good heat release properties. 4,[11][12][13][14][15] Since controlling insulator-semiconductor interfaces is critical for both gate-insulator or passivation applications, it is important to characterize and analyze the interface states. In fact, we observe frequency dispersion in C-V characteristics of MIS devices, attributed to electron trapping/detrapping at interface mid-gap states leading to gate-control impediment.…”
Section: Introductionmentioning
confidence: 99%